Development of mine haul road surfacing condition monitoring through digital image processing - Thompson, Roger; Hahn, S.; Pastor, S. (Society for Mining, Metallurgy and Exploration, Inc, 2015)
As the concept of autonomous haulage systems (AHS) moves from proto-types to production-ready applications, the operating performance of the haul road will become mission critical to the overall success of autonomy in mining. Deterioration in road performance will require remediation, human intervention and significant, albeit temporary, changes to operating procedures, to accommodate road maintenance. With autonomous trucks comes the opportunity to reduce road formation and operating width. This will, therefore, generate potentially significant reductions in stripping ratios and improvements to mine economics, but only if the design of the road, and its associated deterioration rate, is predictable and manageable, based on the materials used to construct the road and the maintenance interventions to be carried out on the road.